Using the Papanicolaou (Pap) smear for cervical cancer screening in a tertiary care hospital: a prospective study and clinical correlation - Devangkumar Patel; Sameer Kadam; Ankita Patel (Golestan University Of Medical Sciences, 2023)
Background: Cervical cancer is the most frequent cause of death for women in developing countries. India, the second-most populous nation in the world, accounts for about 25% of cervical cancer deaths. Even in its premalignant stage, cervical cancer can be detected using a Papanicolaou (Pap) smear test. The goal was to study the role of Pap smear in detecting premalignant, malignant, and non-neoplastic lesions of the cervix and to ascertain the frequency of different lesions. Methods: All women who visited the obstetrics and gynecology outpatient department (OPD) at GMERS Medical College and Hospital, Navsari, India, in 1 year for different clinical problems were recruited. A total of 322 women who were sexually active and over 21 years of age were enrolled in the study. A Pap smear was used for all the women to screen for cervical cancer. The smear was obtained using an Ayre spatula and spread over a marked glass slide, which was placed in 95% ethyl alcohol and sent to the Department of Pathology for cytopathological examination. Women who had visible malignant cervical lesions were excluded. All the data were recorded in a predetermined form. Results: A total of 322 patients were screened. Out of 322, 261 smears were NILM (negative for intraepithelial lesion or malignancy) and 126 (39.1 %) smears had inflammatory changes; 2.2 % and 1.2% smears showed changes as ASCUS (atypical squamous cells of undetermined significance) and ASC-H (atypical squamous cells cannot exclude high-grade squamous intraepithelial lesions), respectively; 4.7 % and 5.3% smears showed LSIL (low-grade squamous intraepithelial lesion) and HSIL (high-grade squamous intraepithelial lesion). Squamous cell carcinoma was observed in only 2 (0.6%) of the smears. A total of 16 (4.9%) smears were unsatisfactory for evaluation because they lacked sufficient squamous components or were obscured by inflammation. Conclusion: The Pap smear test is a very easy, non-invasive, useful, simple, safe, and economical tool to detect preinvasive cervical epithelial lesions. It is evident and proven that every woman above the age of 30-35 years must be subjected to cervical screening, and this must be continued even in the postmenopausal period.